Employees’ attitudes toward the implementation of the nursing process and nursing documentation in psychiatric practice - Jovanovic, Vesna R.; Pavlović Jugović, Katarina; Zigic, Ana; Lazic, Slavica; Stepanovic, Ivana; Dabic, Marijana (Education and Research in Health Sciences, 2026)
Introduction: The nursing process represents a standardized methodological framework in professional nursing practice. Its implementation and documentation are particularly important in psychiatric settings, where care is based on a biopsychosocial approach and interdisciplinary teamwork. Despite being an integral part of formal nursing education, the application of the nursing process in clinical practice remains inconsistent, especially in mental health care.Aim: The aim of this study was to examine employees’ attitudes toward the significance and possibilities of implementing nursing documentation in interdisciplinary teamwork in psychiatric care.Methods: A descriptive, cross-sectional study was conducted. The sample consisted of 39 employees of different professional profiles involved in the care, treatment, and psychosocial support of persons with mental disorders at the Home for Persons with Mental Disorders “1. oktobar”, Stari Lec, Serbia. Data were collected using a structured questionnaire developed for the purposes of this study and analyzed using descriptive statistical methods.Results: The results showed that the majority of participants were not fully familiar with the nursing process (71.8%); however, they recognized the importance of nursing documentation for the quality of care, patient safety, and intervention planning within teamwork (82.1%). In practice, documentation most often referred to selected implemented interventions, while consistent application and documentation of all phases of the nursing process were limited (23.1%). Overall, participants expressed positive attitudes toward the potential improvement of nursing practice through the implementation of standardized nursing documentation.Conclusion: The findings indicate a gap between the theoretical importance of the nursing process and its practical application in psychiatric settings. Although employees acknowledge the significance of nursing documentation in interdisciplinary teamwork, further efforts are needed to support its consistent implementation through continuous education, improved documentation systems, and stronger institutional support.
Keywords: nursing process; nursing documentation; psychiatry; teamwork; employees' attitudes